2018
DOI: 10.1111/gfs.12365
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of alfalfa improves nutritive value and in vitro digestibility of various straw–grass mixed silages in Tibet

Abstract: To enlarge the feed resources and enhance the utilization efficiency of straws as ruminant feed in Tibet, four kinds of local crop straws with tall fescue (Festuca arundinacea Schreb.) based on the ratio of 40/60 (fresh weight) were ensiled with four levels (0, 10%, 20% and 30% of fresh weight) of alfalfa (Medicago sativa L.), respectively. The laboratory silos (1L) were opened after 45 days of ensiling, and the fermentation characteristics, nutritive value and in vitro digestibility of the mixed silages were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The higher LA and AA contents have been observed in all treatments and the lowest pH values in S7Y3. This could be explained by more organic acids produced when silage was mixed with high WSC and moisture content forages (Wang et al, 2018). Xue et al (2017) also indicated that desert wormwood ensiled with highmoisture maize (corn) straw had lower pH and AA concentration and higher LA concentration as the proportion of desert wormwood decreased.…”
Section: Fermentative Quality Of the Silagesmentioning
confidence: 97%
“…The higher LA and AA contents have been observed in all treatments and the lowest pH values in S7Y3. This could be explained by more organic acids produced when silage was mixed with high WSC and moisture content forages (Wang et al, 2018). Xue et al (2017) also indicated that desert wormwood ensiled with highmoisture maize (corn) straw had lower pH and AA concentration and higher LA concentration as the proportion of desert wormwood decreased.…”
Section: Fermentative Quality Of the Silagesmentioning
confidence: 97%
“…In vitro gas production measurements are an effective way to detect silage quality. Thus, many researchers have evaluated the digestibility of feed by this technology [ 35 ]. The amount of in vitro gas production was closely related to the rate of degradation of carbohydrates contained in the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . (2018) evaluated legume herbage substitution in various straw silages and found the IVDMD was positively correlated with the proportion of CP. It implied SPV substitution has a positive effect on providing more digestible substrate in the rumen digestion.…”
Section: Discussionmentioning
confidence: 99%